2014
DOI: 10.1093/jnci/dju316
|View full text |Cite
|
Sign up to set email alerts
|

Screening Outcomes Following Implementation of Digital Breast Tomosynthesis in a General-Population Screening Program

Abstract: Our data support the clinical implementation of DBT in breast cancer screening; however, larger prospective trials are needed to validate our findings in specific patient subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
95
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(105 citation statements)
references
References 20 publications
5
95
1
4
Order By: Relevance
“…As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37]. DBT is currently being used in Australia as a diagnostic tool, but there is increasing evidence to suggest that it may be beneficial as a screening tool [33][34][35][36]. However, it is common practice to use DBT in conjunction with, rather than instead of, digital mammography, which results in a total examination dose approximately 2-3 times that of digital mammography alone.…”
Section: Advances In Technologysupporting
confidence: 80%
See 2 more Smart Citations
“…As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37]. DBT is currently being used in Australia as a diagnostic tool, but there is increasing evidence to suggest that it may be beneficial as a screening tool [33][34][35][36]. However, it is common practice to use DBT in conjunction with, rather than instead of, digital mammography, which results in a total examination dose approximately 2-3 times that of digital mammography alone.…”
Section: Advances In Technologysupporting
confidence: 80%
“…The main advantage of DBT is that it significantly reduces the effects of superimposition, thereby enabling visualisation of lesions that would be masked by over-or under-lying tissue and distinguishing real lesions from those mimicked by superimposition of normal structures [29]. A number of studies on large screening populations showed an increase in overall cancer detection rate and a reduction in recall rate when using DBT in addition to 2D digital mammography, compared to using 2D digital mammography alone [33][34][35][36]. As expected, the greatest gains in sensitivity were observed for younger women and those with heterogeneously dense breasts [36,37], but interestingly, there was no significant increase in cancer detection in those with extremely dense breasts [37].…”
Section: Advances In Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Hot on the heels of the prospective trials, several retrospective evaluations of DBT in the screening setting have also shown improved detection measures when adjunct DBT is used with mammography: three of these studies [7][8][9] compared detection measures for the same services before and after the introduction of adjunct DBT, one study [10] compared services using standard mammography with services using adjunct DBT within the same timeframe and one study compared contemporaneous groups of women who opted for DBT or for standard screening within community-based radiology services [11]. Although these methodologies provide less direct comparisons for mammography screening with and without adjunct DBT than the prospective studies (which provided within subject comparisons), they also found increased breast cancer detection attributable to DBT in the range of 0.5-1.4/1000 screens [7][8][9][10][11].…”
mentioning
confidence: 99%
“…One appeal is the reduction of false-positives (approximately 15%) and increased cancer detection rates (approximately 28%; for invasive cancers, 40% or more) [121][122][123] , together with a onethird reduction in recall rates and consequent false-positive biopsies 117,124,125 , especially in younger women and women with dense breasts in whom mammography is limited, and with no negative effect on sensitivity 123,[126][127][128] , which could potentially tip the risk:benefit ratio toward tomosynthesis 129,130 . And although compared with mammography alone, tomosynthesis roughly doubles total radiation exposure, this can be obviated using the synthesized 2D images created from the three-dimensional tomosynthesis dataset, dramatically reducing the radiation (43% or more) to that of a standard mammogram (eliminating separate 2D exposures), with superior lesion visualization for microcalcification cluster detectability [131][132][133][134][135] , and having the potential to render conventional 2D mammography obsolete 117,123,[135][136][137][138][139][140] .…”
Section: New Screening Modalities: Digital Breast Tomosynthesismentioning
confidence: 99%